Sistema de monitorización continua IoT para la prevención contra sobrecargas mecánicas en motores de inducción de hasta 50 Nm y 3200 rpm - Marín Asendra, Daniel Andrés; Moreno Aldana, Emanuel Alexander (Universidad Antonio Nariño, 2024)
This work presents the design and implementation of an IoT system for continuous monitoring of torque and speed in induction motors, aimed at preventing mechanical overloads. The proposed system utilizes strain gauges and an optical encoder to convert physical variables into electrical signals. These signals are captured by an ESP32 microcontroller and subsequently transmitted to a database through IoT protocols.